D’Héraclée à Ausculum : les traditions historiographiques - Emmanuèle Caire (Pallas, 2009)
The many divergences and contradictions presented by Antique testimonies, often fragmentary, concerning Pyrrhos’s campaign in Italy, have led modern historians to inquire into the constitution of source families. The present case study which bears on the diplomatic and military strategy followed by Pyrrhos after the battle of Heraclea, invites one to reconsider the commonly agreed hypothesis according to which Appianos’ account would derive from an original annalistic tradition while that of Dion/Zonaras would be the precise trustworthy testimony of the Livian tradition.